2010
DOI: 10.1016/j.joca.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Quality of scaffold fixation in a human cadaver knee model

Abstract: This study showed that optimal fixation cannot be combined always with high scaffold integrity. Special attention devoted to scaffold properties in relation to the fixation technique may result in an improvement of scaffold fixation, and thus clinical cartilage regenerative approaches involving these scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 23 publications
0
47
0
Order By: Relevance
“…The closest approximation to the natural environment is offered by the human cadaveric hip, which could be used to simulate the gait cycle in the post-operative rehabilitation period 10,12 . Previous studies testing cartilage repair in a cadaveric model have used simple sinus cyclic loading in both the knee and hip joint 19,21,36 . Fontana et al have recently reported on the stability of polydioxanone scaffolds in a cadaveric hip joint using continues passive motion performed by a manual operator 36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The closest approximation to the natural environment is offered by the human cadaveric hip, which could be used to simulate the gait cycle in the post-operative rehabilitation period 10,12 . Previous studies testing cartilage repair in a cadaveric model have used simple sinus cyclic loading in both the knee and hip joint 19,21,36 . Fontana et al have recently reported on the stability of polydioxanone scaffolds in a cadaveric hip joint using continues passive motion performed by a manual operator 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first study to compare four different cartilage repair techniques in a human cadaveric hip joint under physiological loading. A complete gait cycle at 25% weight bearing was used to simulate the initial phase of rehabilitation after cartilage repair techniques and while other studies have used an end point of maximum of 300 cycles 19,21 , in this study an endpoint of 1500 gait cycles was used, which is equivalent to half a day of walking in the average healthy individual 32e34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Polyactive scaffold was prepared as previously described [18]. In brief, PEOT-PBT co polymer granules (PoroGen BV, The Netherlands) with a 1000/70/30 composition (70/30 PEOT/PBT and a PEG molecular weight of 1000) were printed using a 3D fiber deposition technique [19] with the BioScaffolder system (SysEng, Germany).…”
Section: Materials and Methods N Chondrocyte Isolation And Expansionmentioning
confidence: 99%
“…The method can be supported by applying biodegradable pins, fibrin glue, and cartilage or transosseous sutures [4][5][6][7]. However a sufficiently firm fixation through these techniques is scarcely compatible with the preservation of the scaffold integrity.…”
Section: Introductionmentioning
confidence: 99%